Alternate Formulations for Static Multi-Attribute Assignment Models - Srinivasan, V.; Thompson, G. L. (Management Science, 1973)
In an earlier issue of this journal, Charnes, Cooper, Niehaus and Stedry provided different problem formulations to take into account the multiple attributes that organizations may consider in assigning men to jobs. The present paper shows that their formulations for static multi-attribute models (i.e., when assignments are time independent) can be reformulated either as standard assignment problems or as bottleneck assignment problems by suitably redefining the cost coefficients, with the result that optimal solutions with integer assignments can be guaranteed.